Cognition and psychopathology in first-episode psychosis: are they related to inflammation?. Issue 10 (8th April 2016) - Cabrera, B.; Bioque, M.; Penadés, R.; González-Pinto, A.; Parellada, M.; Bobes, J.; Lobo, A.; García-Bueno, B.; Leza, J. C.; Bernardo, M.
Abstract : Background: Cognitive deficits are present from the onset of psychosis and are considered a core feature of the disorder. Increasing evidence suggests that cognitive function is associated with inflammatory processes. This study evaluated the association between cognition and inflammatory biomarkers in first-episode psychosis (FEP), in order to identify cognitive phenotypes from inflammatory expression profiles. Method: A case-control study of 92 FEP patients and 80 matched controls was used. Neurocognitive assessment, including verbal ability, sustained attention, verbal memory, working memory and executive function, was performed. The expression of pro- and anti-inflammatory mediators of the main intracellular inflammatory pathway was measured in peripheral blood mononuclear cells and plasma. Results: FEP patients performed worse in all cognitive domains compared to controls and had higher expression of pro-inflammatory mediators and lower expression of anti-inflammatory mediators. In the FEP group, cognition and psychopathology were associated with inflammation. Hierarchical regression analysis showed that association between the anti-inflammatory prostaglandin 15d-PGJ2 and sustained attention on one hand, and COX-2 expression and executive function on the other, were statistically significant. Conclusions: Our study provides evidence for an association between anti-inflammatory biomarkers and cognition in FEP. The identification of a subgroup of patients based on these measures could be useful to guide treatment programmes by providing tools to select a personalized treatment approach, but longitudinal studies are needed before. In the future, establishment of biomarkers linked to cognition would be useful to monitor the course of cognitive impairment, but substantially more data will be required. Determination of I κ B α, the inhibitory protein of the pro-inflammatory transcription factor NF κ B, could be useful in early phases to assess clinical severity.